Silvered Langur (Trachypithecus cristatus) Survey in Sibuti Wildlife Sanctuary, Miri, Sarawak - Wan Nur Syafinaz, Wan Azman; Norfarhana, Mazlan; Muhammad Farhan, Abd Wahab; Abdul Ajis, Taib; Sunni, Mali; Faisal Ali, Anwarali Khan (2021)
A rapid and passive primate survey using a scanning technique was conducted in Sibuti Wildlife Sanctuary (Sibuti WS) from 11th to 16th July, 2018. This study provided the first confirmed record of the presence and the diet of silvered langur in the wildlife sanctuary. A group of silvered langur that comprise 20 to 30 individuals were observed in the vicinity of the sanctuary. The diurnal langur feeds on fig plants (Ficus sp.), simpoh air (Dillenia suffruticosa) and tree from the family Leguminosae. However, this langur population appears to be isolated and is probably decreasing due to limited food sources, intra- and interspecific competition, and hunting pressure by local people.